Hubungan Antara Adiksi Smartphone dengan Prokrastinasi Akademik pada Siswa SMA Muhammadiyah Tasikmalaya - Munawwaroh, Sofia Rahma (Universitas PGRI Semarang, 2025)
This study aims to look at the relationship between smartphone addiction and student academic procrastination. The measuring instruments used for data collection used smartphone addiction scale and academic procrastination scale given to 184 students. The data analysis technique used descriptive analysis and correlation test. The results showed that smartphone addiction and academic procrastination obtained a significance of 0.00, then the correlation coefficient of 0,533. Based on the results of the study, there is a positive relationship between smartphone addiction and academic procrastination. If the higher the smartphone addiction, the higher the academic procrastination. Vice versa, the lower the smartphone addiction, the lower the academic procrastination.